Morphometric and molecular analysis of variation in the southern African hedgehog, Atelerix frontalis (Eulipotyphla : Erinaceidae) - Bastos, Armanda D.S. (University of Pretoria, 2013)
Dissertation (MS)--University of Pretoria, 2011.